To find \( (f \circ g)(x) \), we need to substitute \( g(x) \) into \( f(x) \).
We have:
- \( f(x) = 5x - 5 \)
- \( g(x) = 6 - 2x \)
Now we'll find \( (f \circ g)(x) \):
\[ (f \circ g)(x) = f(g(x)) = f(6 - 2x) \]
Next, substitute \( 6 - 2x \) into \( f(x) \):
\[ f(6 - 2x) = 5(6 - 2x) - 5 \]
Now distribute \( 5 \):
\[ = 30 - 10x - 5 \]
Combine like terms:
\[ = 25 - 10x \]
So,
\[ (f \circ g)(x) = 25 - 10x \]
Now for \( (g \circ f)(x) \), we substitute \( f(x) \) into \( g(x) \):
\[ (g \circ f)(x) = g(f(x)) = g(5x - 5) \]
Substituting into \( g(x) \):
\[ g(5x - 5) = 6 - 2(5x - 5) \]
Distributing \( -2 \):
\[ = 6 - 10x + 10 \]
Combining like terms:
\[ = 16 - 10x \]
So,
\[ (g \circ f)(x) = 16 - 10x \]
In summary:
\[ (f \circ g)(x) = 25 - 10x \] \[ (g \circ f)(x) = 16 - 10x \]